Pengaruh Komponen Neraca Air Terhadap Produktivitas Kelapa Sawit pada Berbagai Jenis Tanah:: Studi Kasus Kalimantan Tengah dan Barat - Adhy Ardiyanto; Kukuh Murtilaksono; Enni Dwi Wahjunie; Atang Sutandi (Jurnal Penelitian Kelapa Sawit, 2021)
Different types of soil and the geographical areas of oil palm plantations generate variations in soil physical properties (e.g. texture and porosity). Differences in geographical location further result in variations in the amount of rainfall that affects the water balance. The response to diverse fluctuations in palm oil production due to variations in soil types and water balance can be assessed through correlation analysis between water balance parameters and oil palm productivity under varying soil types and regions. In this study, the water balance analysis was carried out at three locations of PT Bumitama Gunajaya Agro's oil palm plantations in Central Kalimantan and West Kalimantan provinces, using the Thornthwaite-Mather method. Analysis of the relationship between water balance components and oil palm fresh fruit bunch (FFB) yields is calculated based on monthly data for 8 years (2012 - 2019) using time series analysis and stepwise regression to find the best regression model. The water balance components that most influence the fresh fruit bunches (FFB) yield (tonnes/ha/month) are rainfall 7 months before harvest, rainy days 11 and 28 months before harvest, and water deficit 10 months before harvest. A decrease in FFB yield (tonnes/ha/month) occurs every time there is an increase in water deficit of 10 mm/month on Dystrudept, Paleudults, and Haplohumods soils in Area 3, respectively 11, 2, and 3%. In Area 5 the decline is 12, 4, and 5%. In Area 6 the decline is 5, 18, and 3%.